An Overview of Herbal Products and Secondary Metabolites Used for Management of Type Two Diabetes - Ota, Ajda; Ulrih, Nataša P. (Frontiers in Pharmacology, 2017)
Diabetes mellitus is a common effect of uncontrolled high blood sugar and it is associated with long-term damage, dysfunction, and failure of various organs. In the adult population, the global prevalence of diabetes has nearly doubled since 1980. Without effective prevention and management programs, the continuing significant rise in diabetes will have grave consequences on the health and lifespan of the world population, and also on the world economy. Supplements can be used to correct nutritional deficiencies or to maintain an adequate intake of certain nutrients. These are often used as treatments for diabetes, sometimes because they have lower costs, or are more accessible or ‘natural’ compared to prescribed medications. Several vitamins, minerals, botanicals, and secondary metabolites have been reported to elicit beneficial effects in hypoglycemic actions in vivo and in vitro; however, the data remain conflicting. Many pharmaceuticals commonly used today are structurally derived from natural compounds from traditional medicinal plants. Botanicals that are most frequently used to help manage blood glucose include: bitter melon (Momordica charantia), fenugreek (Trigonella foenum graecum), gurmar (Gymnema sylvestre), ivy gourd (Coccinia indica), nopal (Opuntia spp.), ginseng, Russian tarragon (Artemisia dracunculus), cinnamon (Cinnamomum cassia), psyllium (Plantago ovata) and garlic (Allium sativum). In majority of the herbal products and secondary metabolites used in treating diabetes, the mechanisms of action involve regulation of insulin signalling pathways, translocation of GLUT-4 receptor and/or activation the PPAR gamma. Several flavonoids inhibit glucose absorption by inhibiting intestinal α-amylase and α-glucosidase. In-depth studies to validate the efficacies and safeties of extracts of these traditional medicinal plants are needed, and large, well designed, clinical studies need to be carried out before the use of such preparations can be recommended for treatment and/or prevention of diabetes. The main focus of this review is to describe what we know to date of the active compounds in these, along with their glucose-lowering mechanisms, which are either through insulin-mimicking activity or enhanced glucose uptake.